Utilization of â€œBocah Pejuangâ€ TV Show of Trans TV to Improve Social Intelligence in Student on Social Studies Learning - Yusuf, Riyan Nuryana; Abdulkarim, Aim; Kurniawati, Yeni (Universitas Pendidikan Indonesia, 2018)
This research is related to the utilization of the â€œBocah Pejuangâ€ tv show of trans tv in the social studies learning to improve students' social intelligence which aims to explain how the planning, implementation, improvement and the constraints and solutions that arise in social studies learning. The method used in this research is Classroom Action Research using Kemmis and Taggart model. Data collection was conducted in class VIII A 44 Bandung Junior High School by using the method of observation and interview. The theory used is the theory of social intelligence from Suyono (2007). The results showed that the utilization of theÂ â€œBocah Pejuangâ€ tv show can be used as an alternative to improve students' social intelligence. Planning should be done before the lesson by preparing learning pimplementation plan, model, method, and instructional media by using the â€œbocah pejuangâ€ show; implementation of learning according to the planning that has been done; an increasing and significant indicator of social intelligence seen in improved discipline, empathy ability, and communication skills; as well as constraints and solutions encountered in broad outline that is the lack of experience of teachers in utilizing television shows to be a medium of learning so that difficulty in determining the appropriate impressions and in accordance with the purpose of learning. This study recommends that teachers and the school can utilize the media and learning resources close to the lives of students, especially impressions that have positive values in order to improve the competence of other students